ECO-FRIENDLY PACKAGING IMPLEMENTATION THROUGH COMPOSITE CANS FOR SOLO SOUVERNIR PRODUCTS - Prameswari, Nadia Sigi; Al-Faruq, Moh. Yudik; Krisnawati, Maria; Paranti, Lesa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Abstract. Solo's specialty souvenir products have great potential to develop as a cultural identity as well as a superior regional economic commodity. Ironically, many souvenir products still use packaging that is not visually attractive, has minimal information, and does not reflect local characteristics. This study aims to develop packaging design innovation through the application of composite cans as an eco-friendly alternative for Solo's specialty souvenir products. The study focused on the process of designing visual label designs, selecting packaging materials, and the stages of production and design evaluation. The method used was a descriptive qualitative approach with field observation and design experiments. The design process included the development of a visual identity implemented on the packaging label applied to composite cans measuring 9.9x7 cm and 7.3x17 cm. The results of the study showed that composite can packaging was able to provide visual appeal that had an impact on the selling value of the product. The design of the packaging label strengthens the image of Solo's specialty culinary products that are authentic, high quality and have high selling value. This innovation is expected to help MSMEs compete in a wider market with packaging that is superior in terms of aesthetics, functionality, and sustainability.